A study of entrepreneurial intention among accounting students: a case of UiTM Kedah and UiTM Perlis / Mazlifa Md Daud ...[et al.] - Md Daud, Mazlifa; Mohd Saad, Sazilah; Abd Rahim, Maisarah; Abdullah, Wan Nailah (Research Management Institute, 2010)
In reality, the involvement of graduates in entrepreneurship is still at a somewhat low level. This shows that the government’s expectation of high involvement of graduates in entrepreneurship is not yet achievable. A gap exists between what is expected by the government on our graduates and the actual scenario of involvement among graduates in entrepreneurship. Here lies a gap that needs further investigation in explaining graduate attitude and behaviour towards entrepreneurship. A total of 193 final year diploma and degree in accounting students both from UiTM Kedah and UiTM Perlis were interviewed using structured questionnaire. This study provides an insight on the association of Theory of Planned Behaviour with entrepreneurial intention and it helps to explain the level of intention formation among students and it is based on their demographic background. This study found that all determinants were positively correlated with entrepreneurial intention among final year undergraduate accounting students. It also provides some valuable input to the university policy makers, the government and entrepreneurship agencies in generating potential entrepreneurs and promoting entrepreneurship as a career choice among future students. Future research is suggested to introduce moderator variable such as government entrepreneurial grant and scheme for young graduate improve the predictions of entrepreneurial intention.